Effect of inert gas blowing on the microstructure and mechanical properties of semi-solid cast Al–20 %Mg2Si composite - Moein G. Shabestari; Ahad Nasimi Asl; Saeed G. Shabestari (Journal of Materials Research and Technology)
The morphology and particle size of the primary Mg2Si intermetallic compounds significantly influence the mechanical properties of the in-situ Al–Mg2Si composite. This study investigates, for the first time, the effect of argon inert gas blowing in the semi-solid state or gas induced semi-solid (GISS) at varying durations, flow rates, and temperatures on the microstructure, hardness, and tensile properties of the Al–20 %Mg2Si in-situ composite. Additionally, GISS operations were conducted to evaluate the increase in entry points for the inert gas into the melt, utilizing two diffusers separately on a fixed sample. microstructural evaluations revealed that the sample produced at 660 °C, with a flow rate of 6 L min−1 using two graphite diffusers for 20 s, exhibited an average particle size of 32 μm for the primary Mg2Si, a sphericity of 65 %, and a primary Mg2Si particle count of 405 per mm2. These findings represent a significant microstructural improvement compared to the as-cast sample, underscoring the novelty of this work in modifying Mg2Si intermetallic by inert gas blowing. Results from tensile and hardness tests demonstrated that for the optimal sample, hardness increased by 32 %, ultimate tensile strength (UTS) by 18 %, yield strength (Y.S.) by 12 %, elongation (ɛ%) by 39 %, toughness by 66 %, in comparison to the as-cast sample, indicating substantial enhancement in mechanical properties.